Impact of Genetic Variations in HIV-1 Tat on LTR-Mediated Transcription via TAR RNA Interaction - Ronsard, Larance; Ganguli, Nilanjana; Singh, Vivek K.; Mohankumar, Kumaravel; Rai, Tripti; Sridharan, Subhashree; Pajaniradje, Sankar; Kumar, Binod; Rai, Devesh; Chaudhuri, Suhnrita; Coumar, Mohane S.; Ramachandran, Vishnampettai G.; et al. (Frontiers in Microbiology, 2017)
HIV-1 evades host defence through mutations and recombination events, generating numerous variants in an infected patient. These variants with an undiminished virulence can multiply rapidly in order to progress to AIDS. One of the targets to intervene in HIV-1 replication is the trans-activator of transcription (Tat), a major regulatory protein that transactivates the long terminal repeat (LTR) promoter through its interaction with trans-activation response (TAR) RNA. In this study, HIV-1 infected patients (n=120) from North India revealed Ser46Phe (20%) and Ser61Arg (2%) mutations in the Tat variants with a strong interaction towards TAR leading to enhanced transactivation activities. Molecular dynamics simulation data verified that the variants with this mutation had a higher binding affinity for TAR than both the wild-type Tat and other variants that lacked Ser46Phe and Ser61Arg. Other mutations in Tat conferred varying affinities for TAR interaction leading to differential transactivation abilities. This is the first report from North India with a clinical validation of CD4 counts to demonstrate the influence of Tat genetic variations affecting the stability of Tat and its interaction with TAR. This study highlights the co-evolution pattern of Tat and predominant nucleotides for Tat activity, facilitating the identification of genetic determinants for the attenuation of viral gene expression.